Reference study of CityGML software support: The GeoBIM benchmark 2019—Part II. Issue 2 (30th November 2020) - Noardo, Francesca; Arroyo Ohori, Ken; Biljecki, Filip; Ellul, Claire; Harrie, Lars; Krijnen, Thomas; Eriksson, Helen; van Liempt, Jordi; Pla, Maria; Ruiz, Antonio; Hintz, Dean; Krueger, Nina; et al.
Abstract: OGC CityGML is an open standard for 3D city models intended to foster interoperability and support various applications. However, through our practical experience and discussions with practitioners, we have noticed several problems related to the implementation of the standard and the use of standardized data. Nevertheless, a systematic investigation of these issues has never been carried out, and there is thus insufficient evidence for tackling the problems. The GeoBIM benchmark project is aimed at finding such evidence by involving external volunteers, reporting on various aspects of the behavior of tools (geometry, semantics, georeferencing, functionalities), analyzed and described in this article. This study explicitly pointed out the critical points embedded in the format as an evidence base for future development. A companion article (Part I) describes the results of the benchmark related to IFC, the counterpart of CityGML within building information modeling.